Isolation and characterization of antibacterial compounds from a Garcinia livingstonei (Clusiaceae) leaf extract - Eloff, Jacobus Nicolaas (University of Pretoria, 2013)
Dissertation (MSc (Veterinary Science))--University of Pretoria, 2009.